2021
DOI: 10.22454/fammed.2021.808187
|View full text |Cite
|
Sign up to set email alerts
|

“Am I Making More of It Than I Should?": Reporting and Responding to Sexual Harassment

Abstract: Background and Objectives: Health professionals may face sexual harassment from patients, faculty, and colleagues. Medicine’s hierarchy deters response to sexual harassment. Current evidence consists largely of quantitative data regarding the frequency and types of sexual harassment. More information is needed about the nature of the experience and how or why professionals choose to report or respond. Methods: We developed and administered a semistructured interview guide to elicit family medicine faculty and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Our department of family medicine (FM) found that SH and GB were frequently experienced by most women, yet most were hesitant to report or respond. 1 Respondents cited fear as a barrier on a continuum of interpersonal-level fear of reporting, from being seen as someone who "takes the fun out" of work, to "losing opportunities for career advancement." 1 Respondents' experience of SH and GB is associated with lasting psychological effects that mainly spared the men in our department.…”
Section: Introductionmentioning
confidence: 99%
“…Our department of family medicine (FM) found that SH and GB were frequently experienced by most women, yet most were hesitant to report or respond. 1 Respondents cited fear as a barrier on a continuum of interpersonal-level fear of reporting, from being seen as someone who "takes the fun out" of work, to "losing opportunities for career advancement." 1 Respondents' experience of SH and GB is associated with lasting psychological effects that mainly spared the men in our department.…”
Section: Introductionmentioning
confidence: 99%
“…Health professionals may face sexual harassment and gender bias from patients, peers, superiors, or subordinates. Studies show that almost all women physicians have experienced patient‐related harassment and discrimination, and the experiences often go unreported due to training structures, fear of jeopardizing the patient relationship, and confusion about the reporting process 7 . The number of female dental students and faculty in the U.S. dental institutions is on the rise, and therefore, it is important to consider how the #MeToo movement and Title IX intersect with dental education.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies called to investigate sociocultural influences on the responses of nurses to sexual harassment by patients (Burke, 2019; Russell et al, 2021; Scholcoff et al, 2020; Ulusoy et al, 2011). Currently, studies that examined this phenomenon among religious women or religious nurses are scant.…”
Section: Introductionmentioning
confidence: 99%